2018
DOI: 10.20944/preprints201810.0081.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Comparison of Cohesive Models in EDEM and LIGGGHTS for Simulating Powder Compaction

Abstract: The purpose of this work was analysing the compaction of a cohesive material using different DEM simulators to determine the equivalent contact models and identify how some parameters of the simulations affect the compaction results (maximum force and compacts appearance) and computational costs. For that purpose, three cohesion contact models were tested (‘linear cohesion’ in EDEM; ‘SJKR’ and ‘SJKR2’ in LIGGGHTS). The influence of the particle size d… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Since particles having identical properties were used in this study, the effective “viscosities” of mixtures are assumed to be the same. Mixing simulations for two sets of mono‐sized particles (250 and 500 μm) were performed using the same surface energy (5 J/m 2 ) with processing amplitudes varied from 5 to 10 mm, and fixed processing time of 10 s. Collision shear force was obtained from EDEM, which depends on tangential overlap and tangential stiffness, and is derived from the Mindlin–Deresiewicz theory 59 . Average collision number was evaluated to further assess the mixing process.…”
Section: Numerical Results and Discussionmentioning
confidence: 99%
“…Since particles having identical properties were used in this study, the effective “viscosities” of mixtures are assumed to be the same. Mixing simulations for two sets of mono‐sized particles (250 and 500 μm) were performed using the same surface energy (5 J/m 2 ) with processing amplitudes varied from 5 to 10 mm, and fixed processing time of 10 s. Collision shear force was obtained from EDEM, which depends on tangential overlap and tangential stiffness, and is derived from the Mindlin–Deresiewicz theory 59 . Average collision number was evaluated to further assess the mixing process.…”
Section: Numerical Results and Discussionmentioning
confidence: 99%
“…Within a reasonable timeframe it is not possible to repeat DEM simulations to generate packing compact replicas. Although the packings are randomly generated in the DEM simulations, and the position of the particles may not be identical in replicas, in a study by Ramírez-Aragón et al [ 64 ] it was confirmed that this difference had a negligible impact on the results.…”
Section: Methodsmentioning
confidence: 99%
“…Employing DEM [12,13], or the multi-particle finite element method (MPFEM) [14, 2 15, 16, 17] on model powder materials, the compaction stage has been investigated. Some authors also studied the compaction behavior of model powder materials containing different particle sizes [18,19] and particle size distributions [20]. In particular, the DEM has proved useful to understand the compaction of composite powders with soft (typically metallic) and hard (typically ceramic) particles mixed together [18].…”
Section: Introductionmentioning
confidence: 99%
“…The major part of the numerical and experimental studies concerning the powder compaction is related to composites made of metal-ceramic materials for the powder-metallurgy process. DEM simulations of the compaction of homogeneous refractory materials (alumina, magnesia) have been reported with various sizes of particles [20,21]. However, as far as we know, no study has been reported yet in the literature regarding compaction simulations using DEM to model refractory composites on a mixture of hard particles and a soft binder.…”
Section: Introductionmentioning
confidence: 99%